Electro-optics of polymer-stabilised blue phase liquid crystal in in-plane switching mode. Issue 12 (25th September 2016) - Singh, Arshdeep; Jayoti, Divya; Khushboo,; Malik, Praveen
ABSTRACT: In the present work, polymer-stabilised blue phase liquid crystal ***(PS-BPLC) that exhibit the blue phase (BP) in a temperature range of 312.15 K to 298.15 K has been prepared. The textural and electro-optic studies were performed in the BP range using an in-plane switching (IPS) cell. Platelet-type textures of cubic BP having an average domain size of ~12 µm were observed. The on-state voltage increased with increasing the temperature due to reduced value of the Kerr constant. Further, the hysteresis was found to be reduced from 19.2% to 5.1% by operating the PS-BPLC sample cell at an elevated temperature. GRAPHICAL ABSTRACT: